Effects of rapid or slow body weight reduction on intramuscular protein degradation pathways during equivalent weight loss on rats - Nonaka, Y; Urashima, S; Inai, M; Nishimura, S; Higashida, K; Terada, S (Physiological research, 2017)
The purpose of this study was to compare the effects of short-term fasting-induced rapid weight loss with those of slower but equivalent body weight loss induced by daily calorie restriction on muscle protein degradation pathways and muscle protein content. Male Fischer rats were subjected to either 30 % calorie restriction for 2 weeks to slowly decrease body weight (Slow) or 3-day fasting to rapidly decrease body weight by a comparable level of that of the Slow group (Rapid). The final body weights were about 15 % lower in both the Slow and Rapid groups than in the Con group (p<0.001). The total protein content and wet weight of fast-twitch plantaris muscle, but not slow-twitch soleus muscle, were significantly lower in the Rapid group compared with the control rats fed ad libitum. Substantial increases in the expression ratio of autophagosomal membrane proteins (LC3-II/-I ratio) and polyubiquitinated protein concentration, used as biomarkers of autophagy-lysosome and ubiquitin-proteasome activities, respectively, were observed in the plantaris muscle of the Rapid group. Moreover, the LC3-II/-I ratio and polyubiquitinated protein concentration were negatively correlated with the total protein content and wet weight of plantaris muscle. These results suggest that short-term fasting-induced rapid body weight loss activates autophagy-lysosome and ubiquitin-proteasome systems more strongly than calorie restriction-induced slower weight reduction, resulting in muscular atrophy in fast-twitch muscle.
Keywords: signální transdukce; Rats; Weight Loss; Time Factors; kalorická restrikce; potkani inbrední F344; svalové proteiny; mužské pohlaví; Signal Transduction; Muscle, Skeletal; proteolýza; Fasting; krysa rodu Rattus; Body Weight; Proteolysis; omezení příjmu potravy; zvířata; kosterní svaly; hmotnostní úbytek; tělesná hmotnost; Rats, Inbred F344; časové faktory; Muscle Proteins; Caloric Restriction; Male; Animals